Izbrana aktualna vprašanja koordinacije dajatev za brezposelnost v Sloveniji - Rataj, Primož (Delavci in delodajalci, 2022)
The contribution is centred on the rules concerning coordination of unemployment benefits that have been under the spotlight in the European Union and in Slovenia in the last few years. The goal of the contribution is to frame and legally discuss some selected issues that are theoretically and practically of greater importance in Slovenia, taking into account that cross-border cases with Austria and partially with Italy are prevalent. The selected issues regard aggregation of periods of insurance, employment and self-employment, frontier workers and reimbursement of unemployment benefits, and legal lacunas in coordination rules. By pointing out the (in)consistencies the contribution indicates the legal framework, upon which the European Union Member States cannot agree, more precisely about the need to alter the rules of the coordination Regulation.
Keywords: aggregation of periods; Brezposelnost; coordination; delovna razmerja; delovno pravo; Evropska unija; frontier workers; legal lacuna; obmejni delavci; reimbursement; unemployment benefit